"Pimping" in Pharmacy Education: A Survey and Comparison of Student and Faculty Views. (June 2018) - Williams, Eric A.; Miesner, Andrew R.; Beckett, Emily A.; Grady, Sarah E.
Background: "Pimping" is an informal teaching technique that is widely used in medical education. Pimping is characterized by questioning the learner with the intent of reinforcing clinical hierarchy. To date, there are no studies of the use of pimping in pharmacy education. Objectives: To describe the use of pimping as a teaching method in pharmacy education and to compare student and faculty perceptions of this technique. Methods: Faculty and fourth-year PharmD (P4) students from 2 colleges of pharmacy were invited to participate in a survey about experiences and perceptions of pimping. Faculty and P4 surveys each contained up to 17 items to assess personal experiences, utilization, perceived risks and benefits, and preferences regarding the role of the technique in pharmacy education. Results: The response rate was 49.5% (159 of 321). Of faculty, 74.1% reported they had been pimped in their training, but less than half (45.8%) use pimping themselves. Similarly, 73.7% of students reported that they had been pimped at some time in their pharmacy education. Students nearly equally viewed their experiences as positive (35.3%) versus negative (38.2%). Responses were similar between faculty and students recommending that the method should be avoided entirely ( P = .259), used sparingly ( P = .072), or used consistently ( P = .309). Perceived benefits and risks of pimping were similar between faculty and students, but there were many differences in rationales offered by faculty versus students' perceived rationales. Conclusion: Pimping is common in pharmacy education and its use is controversial. The perceived rationale for use of pimping differs, which may undermine student/faculty relationships.